2009
DOI: 10.1016/j.antiviral.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviral methyltransferase/RNA interaction: Structural basis for enzyme inhibition

Abstract: Flaviviruses are the causative agents of severe diseases such as Dengue or Yellow fever. The replicative machinery used by the virus is based on few enzymes including a methyltransferase, located in the N-terminal domain of the NS5 protein. Flaviviral methyltransferases are involved in the last two steps of the mRNA capping process, transferring a methyl group from S-adenosyl-L-methionine onto the N7 position of the cap guanine (guanine-N7 methyltransferase) and the ribose 2'O position of the first nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
2
64
0
Order By: Relevance
“…Interestingly, mutational analysis of NS5MTase WNV within the viral genome has shown that the 29O-MTase activity is important for WNV reproduction (Zhou et al, 2007). Our 29O-MTase assay will be useful for screening and characterizing potential inhibitors, as already demonstrated by the identification of two flavivirus MTase inhibitors (Luzhkov et al, 2007;Milani et al, 2009). …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, mutational analysis of NS5MTase WNV within the viral genome has shown that the 29O-MTase activity is important for WNV reproduction (Zhou et al, 2007). Our 29O-MTase assay will be useful for screening and characterizing potential inhibitors, as already demonstrated by the identification of two flavivirus MTase inhibitors (Luzhkov et al, 2007;Milani et al, 2009). …”
Section: Resultsmentioning
confidence: 97%
“…NS5MTase DV did not show any N7-MTase activity on the substrate GpppAC n . The N7-MTase activity of NS5MTase DV has been demonstrated on long (190 nt) specific RNA substrates corresponding to the 59 end of flavivirus genomes (Dong et al, 2007;Milani et al, 2009). Using 39 end deletions of a WNV substrate, it was shown that the N7-MTase activity of NS5MTase WNV required a 74 nt substrate including the 59 stem-loop A present in all flavivirus genomes (Dong et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme-based screenings or structure-based drug design have identified DENV, WNV, and YFV MTase inhibitors targeting either the SAM/SAH (S-adenosyl-Lhomocysteine, the coproduct of the methylation) binding pocket (26)(27)(28), the cap binding pocket (29), or allosteric sites (30,31). As ZIKV is closely related, we initiated a comparative study of ZIKV MTase with other Flavivirus MTases with the aim of subsequently developing original inhibitors or repurposing inhibitors targeting DENV MTase for antiviral research on ZIKV.…”
mentioning
confidence: 99%
“…ATA was also shown to inhibit the DENV and WNV MTases, with a proposed binding site linked to the KDKE RNA-binding motif. 20 We therefore tested the ability of ATA to disrupt FL-dT10-YFV MTase complexes. Results, shown in Figure 3, indicate that ATA disrupted the binding of FL-dT10 to YFV MTase with an EC 50 = 1.54 ± 0.16 µM, which is close to the IC 50 for ATA inhibition of human DNA MTases DNMT1, 0.68 µM, and DNMT3a, 1.4 µM.…”
Section: Ata a Small-molecule Inhibitor Of Protein Nucleic Acid Intementioning
confidence: 99%
“…18 The inhibitor of nucleic acid binding, aurintricarboxylic acid (ATA), was first identified as a potent inhibitor of DENV and WNV MTases by means of in silico screening. 20 Here we describe a simple high-throughput assay for discovery of inhibitors of flavivirus MTases in which fluoresceinlabeled dT10 (FL-dT10) bound to the YFV MTase is used as a surrogate for the vRNA for the discovery of a new class of flaviviral inhibitors, compounds with vRNA displacement activity. This high-throughput assay works without the immediate need for radioactivity-based enzymatic reactions and is suitable for miniaturization.…”
Section: Introductionmentioning
confidence: 99%